1999
DOI: 10.1117/12.351335
|View full text |Cite
|
Sign up to set email alerts
|

Active range-gated spectrometric standoff detection and characterization of bioaerosols

Abstract: In atmospheric sensing, one application that has demonstrated several impressive successes over the last two decades is LIght Detection And Ranging (LIDAR). With elastic signal returns, this technique remotely provides information such as the particle density and, for a multiple field of view LIDAR, the distribution in size of the aerosols as a function of the range along the probing laser beam. For this type of application, the return signal has the same spectrum than the laser source. Some specific technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Each acquisition, lasting between 5 and 30 seconds, was the result of 500 to 3000 integrated laser pulses. More details on these trials and other results can be found in [9,18].…”
Section: Testing Proceduresmentioning
confidence: 96%
See 1 more Smart Citation
“…Each acquisition, lasting between 5 and 30 seconds, was the result of 500 to 3000 integrated laser pulses. More details on these trials and other results can be found in [9,18].…”
Section: Testing Proceduresmentioning
confidence: 96%
“…First, a model was built to predict the performance of such a device as a function of its numerous design parameters [18]. This model, derived from the classical LIDAR equation for multi-spectral returns and a proposed expression for the bioaerosol fluorescence cross-section, constituted ones of the bases of this work.…”
Section: Introductionmentioning
confidence: 99%
“…The light detection and ranging (LIDAR) techniques are considered as being among the ones best suited to real-time scanning and/or long-term monitoring of the pollution above large areas. Their advantages arise from several factors: (1) light wavelengths commensurate with or close to the PM size, (2) good resolution in terms of distance (5-30 m) and elevation angle (~1 o ), and (3) range of operation (20-30 km) [12]. In a scanning mode of operation, the LIDAR techniques allow one to construct LIDAR maps of the aerosol pollution distribution over large cities, which can be easily juxtaposed with the ground atmospheric monitoring networks.…”
Section: Introductionmentioning
confidence: 99%